2013
DOI: 10.1016/j.schres.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic muscarinic M4 receptor gene polymorphisms: A potential risk factor and pharmacogenomic marker for schizophrenia

Abstract: Although schizophrenia is a widespread disorder of unknown aetiology, we have previously shown that muscarinic M4 receptor (CHRM4) expression is decreased in the hippocampus and caudate-putamen from subjects with the disorder, implicating the receptor in its pathophysiology. These findings led us to determine whether variation in the CHRM4 gene sequence was associated with an altered risk of schizophrenia by sequencing the CHRM4 gene from the brains of 76 people with the disorder and 74 people with no history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
1
21
1
1
Order By: Relevance
“…Surprisingly, the results of the allelic association of the rs2067482 polymorphism with the disease were opposite to the ones reported earlier: Scarr et al found allele C being associated with increased risk of schizophrenia. 16 In contrast, our study identified allele T having higher prevalence in schizophrenia patients ( Table 2). It is hard to explain such inconsistency but several reasons can be discussed.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Surprisingly, the results of the allelic association of the rs2067482 polymorphism with the disease were opposite to the ones reported earlier: Scarr et al found allele C being associated with increased risk of schizophrenia. 16 In contrast, our study identified allele T having higher prevalence in schizophrenia patients ( Table 2). It is hard to explain such inconsistency but several reasons can be discussed.…”
Section: Discussioncontrasting
confidence: 77%
“…7 Thereafter, they reported the synonymous polymorphism rs2067482 in CHRM4 to be associated with an increased risk of schizophrenia. 16 In the current study, we have confirmed an association of the rs2067482 variant with schizophrenia in 449 patients versus 134 healthy subjects. No difference in genotype was detected between patients with and without TD.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Nevertheless, as was pointed out by Rietschel et al, it was difficult to determine the susceptibility gene for schizophrenia based on the genetics data alone due to the strong LD in the region and the potential relevance of several genes in this region. Another study reported an association of a synonymous CHRM4 SNP, which was not analyzed in the current study, with schizophrenia, in a small Australian sample [41]. The implication for the results of the current study is that the CHRM4 SNP could be a marker in LD with a causative SNP in another gene in this region.…”
Section: Cholinergic Receptor Muscarinicmentioning
confidence: 54%